2017
DOI: 10.18632/oncotarget.22166
|View full text |Cite
|
Sign up to set email alerts
|

Retinol dehydrogenase-10 promotes development and progression of human glioma via the TWEAK-NF-κB axis

Abstract: Retinol dehydrogenase-10 (RDH10) is a member of the short-chain dehydrogenase/reductase family, which plays an important role in retinoic acid (RA) synthesis. Here, we show that RDH10 is highly expressed in human gliomas, and its expression correlates with tumor grade and patient survival times. In vitro, lentivirus-mediated shRNA knockdown of RDH10 suppressed glioma cell proliferation, survival, and invasiveness and cell cycle progression. In vivo, RDH10 knockdown reduced glioma growth in nude mice. Microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…For instance, NAMPT can be secreted from microglia, 73 and its inhibitor can prolong GBM‐bearing animals' survival time on accompany by PD‐1 checkpoint blockade. 74 TNFSF12‐TNFRSF12A can modulate glioma progression 75 , 76 and may participate in microglia activation. 77 GDF2‐ACVRL1 can modulate glioma angiogenesis, 78 but its association with microglia was elusive.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, NAMPT can be secreted from microglia, 73 and its inhibitor can prolong GBM‐bearing animals' survival time on accompany by PD‐1 checkpoint blockade. 74 TNFSF12‐TNFRSF12A can modulate glioma progression 75 , 76 and may participate in microglia activation. 77 GDF2‐ACVRL1 can modulate glioma angiogenesis, 78 but its association with microglia was elusive.…”
Section: Discussionmentioning
confidence: 99%
“…DR3 is an important receptor of TWEAK, [15] and TWEAK can activate DR3 to promote NF-κB activation. [16,17] signal protein of TWEAK. [18,19] Research has suggested that TWEAK can directly induce NF-κB activation, while the activated NF-κB can promote angiogenesis and induce cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that RDH10 knockdown suppressed the invasion of glioma cells. [13] However, the role of RDH10 in the migration and invasion in glioma cells requires further investigation. In this study, we confirmed that RDH10 was highly expressed in glioma cells, and downregulation of RDH10 inhibited the invasion of glioma cells.…”
Section: Discussionmentioning
confidence: 99%